Distribusi dan Karakteristik Tempat Perkembangbiakan Aedes aegypti serta Perilaku Masyarakat di Daerah Endemis Demam Berdarah Dengue di Salatiga - Riyani Setiyaningsih; Aryani Pujiyanti; M Choirul Hidajat; Lasmiati lasmiati (Loka Litbang Kesehatan Pangandaran, 2018)
Human behavior in form of less awareness about the environment will cause the increase of mosquito breeding places and lead to increase the dengue vector’s population rising. This research’s purpose was to describe distribution and characteristics of the dengue vector’s breeding place and people behavior in dengue endemic areas in Salatiga. The data collection was done by monitoring larvae and pupa on water container and interviewing community about related behavior. Results showed that larvae tend to be found in water storage containers, household appliances and open unused goods which was located inside the house. Based on the analysis, there is no significant difference between the indoor and outdoor container, the container is closed or open, and sprinkled with temephos or not. Significant differences were found in different types of containers, containers with fish and drained in the last one week. People in DHF endemic area tend to conduct 3M (Menguras/drain and Menutup/close the lid of Water Reservoirs and Mengubur/bury unused container that have potential as breeding places) and do not use fish nor larvacide for dengue vector control. Based on the result of the research, it is necessary to evaluate the community behavior in closing container and also evaluate the resistance of DHF vector mosquito to temephos.